Cardiopulmonary anatomy & physiology essentials for respiratory care - Terry R. Des Jardins (Boston, Massachusetts : Cengage, 2020)
This extremely reader-friendly presentation delivers the most complete, accurate information about the structure and function of the respiratory system. Clear and concise coverage presents even complicated concepts in an understandable format using full-color design and proven learning features that guide you in applying what you've learned to your professional career. Thirteen new Clinical Connections add to the book's total 141 Clinical Connections that link chapter content to today's clinical setting and highlight actual situations that respiratory therapists encounter every day. These features also direct meaningful discussion and strengthen your critical-thinking skills
Keywords: Cardiopulmonary system Anatomy